Alkaloids of Fagraea fragrans (Tembesu) Fruits - Dasril Basir; Miksusanti Miksusanti; Dian Dwita Maizur; Susilawati Susilawati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The aim of this paper is to visualize the alkaloids of Fagraea fragrans fruits therefore the fruits can be scientifically used as herb traditional medicines and phytocosmetics.  Three alkaloids have successfully been identified from those Fagraea fragrans fruits, Loganiaceae. They are gentialutine, gentianine, and isaindigotone. The alkaloids were alternately explored by means of ether and 2% H2SO4 extractions. The sulphuric acid phase was naturalized with ammonium chloride and then extracted with ethyl acetate. The residue were then subjected to silica gel G60 (70-230 mesh) column chromatography and eluted with 40% ethyl acetate in n-hexane. The LC-MS spectral of alkaloids gave the protonated molecular ion peaks at m/z (r.t. minute) = 150.08 (1.39), 176.06 (4.80), and 351.37 (5.24) respectively.